2022
DOI: 10.1007/s10668-021-02015-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender attitude towards environmental protection: a comparative survey during COVID-19 lockdown situation

Abstract: Attitude towards environmental protection is a crucial component in environmental safeguard psychology. It is a psychological tendency expressed by evaluating the environmental gender attitude with favour or disfavour. This study aimed to compare the attitude level of male and female trainees towards environmental protection based on personal, psychological and sociocultural variables by using an ex post facto research design. The research population was composed of the trainees ( N =177… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 162 publications
2
4
1
1
Order By: Relevance
“…The results do not clarify much about the conclusions reached in previous studies showing that investment in RE and CRE is more likely among men than among women (Broughel & Hampl, 2018;Fraune, 2015). Gender is not significant in this study, in line with Dhenge et al's (2022) conclusion that gender attitudes toward environmental protection are simultaneously influenced by other personal characteristics and by exogenous factors. Anyway, it is remarkable that the "CRE sceptics" and "CRE enthusiasts" clusters, with a bigger concentration of women, show a lower expected return than the "yield investors" cluster, mainly made up of men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results do not clarify much about the conclusions reached in previous studies showing that investment in RE and CRE is more likely among men than among women (Broughel & Hampl, 2018;Fraune, 2015). Gender is not significant in this study, in line with Dhenge et al's (2022) conclusion that gender attitudes toward environmental protection are simultaneously influenced by other personal characteristics and by exogenous factors. Anyway, it is remarkable that the "CRE sceptics" and "CRE enthusiasts" clusters, with a bigger concentration of women, show a lower expected return than the "yield investors" cluster, mainly made up of men.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher education and income levels are found to positively relate to a higher WTI (Broughel & Hampl, 2018;Koirala et al, 2018;Salm et al, 2016). Regarding gender, most studies find that males predominate among current (Fleiß et al, 2017;Fraune, 2015) or potential (Broughel & Hampl, 2018) investors, despite some works pointing at the finding of lower environmental concern among the male population (Dhenge et al, 2022). Finally, previous literature supports that older people are more likely to engage in CRE (Fleiß et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 94%
“…This finding is consistent with recent studies conducted in Ghana, Indonesia, and Ethiopia [20,31,32]. Studies have indicated that women have modestly stronger pro-environmental values than men [33][34][35]. In Korea, it was observed that pro-environmental behaviors among females are affected by their lifestyles and social norms [36].…”
Section: Determinants Of Household Waste Disposal Choices In Multivar...supporting
confidence: 90%
“…The results of this study are in line with Bord and O'Connor (1997) that there is no consensus on the reasons of gender differences related to EA. Considering that gender roles have no effect, men and women have equal status and roles in environmental protection; thus, Dhenge et al (2022) asserted that continuous assistance is required to effectively understand gender roles in environmental protection. Consequently, social media campaigns, government policies, and the involvement of groups such as scientists, extension officers, research organizations, various training programs, students, and universities in environmental protection movements and awareness campaigns are all needed.…”
Section: Resultsmentioning
confidence: 99%
“…This research will also be the basis for policy makers in schools and universities in implementing various environmental education programs. According to Dhenge et al (2022), EA is an important component in environmental protection psychology. This study tries to determine the environmental attitudes of prospective biology teachers throughout Indonesia.…”
Section: Introductionmentioning
confidence: 99%